Recognizing guerilla gardening as a pathway to urban food security and greening in Metro Manila - Anunciado, M.S.; Kimayong, D.; Del Rio, S.; Schreinemachers, P.; Perez, C.; Bonifacio, P. (International Institute of Rural Reconstruction, 2025)
Metro Manila faces rising food costs, limited access to green spaces, climate stress, and high urban density. While formal urban agriculture and greening programs are in place, many dense and low-income neighborhoods remain underserved. In response, residents have adopted guerrilla gardening or informal planting, growing food and greenery in idle, underused, or public spaces such as sidewalks, road easements, traffic islands, and vacant lots. Despite being widespread and socially accepted, these practices remain largely unrecognized in policy, limiting their sustainability and contribution to urban food systems.